Athletes, acclamations, and imagery from the end of antiquity. (15th November 2017) - Dunbabin, Katherine M. D.
Abstract : In recent years there has been considerable scholarly interest in athletic contests in late antiquity and in the fate of the agonistic festivals that for many centuries constituted the principal occasion for them in the Greek world. The old notion that the end of the games at Olympia, and, a fortiori, that of the other great festivals of the periodos, came with the banning of pagan sacrifice by Theodosius I in A.D. 392/393 is now acknowledged to be wrong; but the evidence for these and most other agones after the beginning of the 5th c. is scanty. Some may have vanished earlier, and most of those that survived then may not have lasted very long after this date. In the West, agones of Greek type had always been very much rarer, but at Rome the Capitolia and Heliaea are attested in the mid- to late 4th c. but similarly vanish from the record at least after the early 5th c. But the absence of later evidence for agones of the traditional Greek type should not be taken to imply the disappearance of athletic contests; there were other occasions on which they could be offered, which need to be more fully acknowledged.